Trophoblast-derived interleukin 9 mediates immune cell conversion and contributes to maternal-fetal tolerance. (November 2021) - Sun, Yi; Wu, Suwen; Zhou, Qiongjie; Li, Xiaotian
Highlights: Semi-allogeneic trophoblasts selectively express HLA to escape from maternal immune recognition and induce immune tolerance. Trophoblast cells also secreted immune factors, such as IL9, with immune cell-like characteristic. Trophoblast derived IL9 mediated conversion of CD14+ DCs and naïve CD4+ T cells, contributing to maternal-fetal tolerance. Abstract: In the maternal-fetal crosstalk, fetal derived trophoblast cells can secret several molecules to regulate immune tolerance such as cytokines and chemokines, besides human leukocyte antigens (HLA) providing. However, the mechanism of these factors in pregnancy is still unknown. Our previous study showed that IL9 could be secreted by trophoblasts and exerted a positive effect on trophoblasts themselves through autocrine signaling. Given the immunoregulatory function of IL9 and its expression in trophoblasts, we hypothesize that IL9 contributes to maternal-fetal tolerance by regulating immune cells, especially CD14+ dendritic cells (DCs) and naïve CD4 + T cells who have essential roles in maternal-fetal immune tolerance. We performed a series of experiments, finding that HTR8/SVneo cells could secrete IL9 in vitro, and this secretion was decreased under hypoxia; both CD14 + DCs and naïve CD4 + T cells expressed IL9 receptors, indicating potential interactions among these cells. In CD14 + DCs, trophoblast-derived IL9 promoted the immature differentiation, and induced the secretion of Th2 cytokines, including IL4 and IL10, shifting the Th1/Th2 ratio to Th2. In naïve CD4 + T cells, IL9 also increased Foxp3 expression and promoted the secretion of Treg cytokines, including TGFβ and IL10, inhibiting pro-inflammatory Th17. Therefore, trophoblasts may act as fetal-derived immune cells to maintain maternal-fetal tolerance by secreting IL9. Given that trophoblast derived IL9 is decreased in preeclampsia, our study provides a new insight into maternal-fetal immunology and immunological disorders in abnormal pregnancy.